Boiler-feed and process water reclamation from Biotreated Palm Oil Mill Effluent (BPOME): A developmental review - Jami, Mohammed Saedi; Amosa, M. K.; Al-Khatib, Ma'an Fahmi Rashid; Jimat, Dzun Noraini; Muyibi, Suleyman Aremu (Croatian Society of Chemical Engineers, 2013)

(untitled)
Increased water shortages and new environmental policies and regulations have stimulated significant development in reuse programs in the past 20 years.1 Reclaimed water has been recognized as a vital and drought-proof water source to ensure economic and agricultural activities. According to the conclusions of various water reuse surveys, the best water reuse projects, in terms of economic viability and public acceptance, are those that substitute reclaimed water in lieu of potable water for use in industrial, irrigation, environmental restoration, cleaning and toilet flushing. The main benefits of using reclaimed water in these situations are conservation of water resources and pollution reduction. 1 Low Pressure Membranes (LPMs) such as Microfiltration (MF) and Ultrafiltration (UF) integrated with adsorption system could be a viable option for separation of contaminants in wastewater for reuse as boiler-feed or process water in industry. This article technically discusses the main constituents of concern in boiler-feed and process water requirements and finally suggests potentially efficient and low-energy-low-cost hybridized LPM /adsorption treatment facilities to achieve this paradigm shift towards new water sources.